Turkey : the interface country between Orient and Occident and the fashion visual communication - Weiand, Roberta (2009)
Turkey is an interface country between Eastern and Western cultures, therefore representing an excellent “case study” concerning the meeting of cultures: Occident versus Orient, Europe versus Asia. This paper takes an approach to fashion as a social and cultural phenomenon, therefore capable of communicating and reflecting the cultural identity “traces of a given society. Knowing the importance of visual codes for the communication of the fashion message, we conducted this work, where the image of fashion is the "central pivot" to understand the cultural identity of this Country.